Ecosystem Modeling with External Data Spatial Temporal in Iraqi Marshland - Estabraq Mohammed Ati (Journal of Global Pharma Technology, 2018)
The impacts of human activities and climate change on Iraqi marshes ecosystems that are challenged limitations of present-day ecosystem models, this research presented a part of a larger study to develop a new approach to ability interaction six main stations of the Missan governorate (Al- Auda Marsh, Al- Battat Marsh) between metals (Cu, Fe, Pb) by geographic information systems (GIS) technology into a flexible and modular software approach to illustrate capabilities of the new framework. Have been predictive abilities of the concentration elements between plants and soil model and applied this framework showed changes at the plants level due to changes in production species. The results in all stations under study showed low concentrations and varied mostly similarly limiting factors with natural boundaries, A little increase come from of some pollutants that are discharged from waste populated. The correlation showed significantly between these variables in the aquatic environment, It would be transmitted an ecological balance between plants and soil. This considered as a very important database for environmental risks and health in aquatic ecosystem of marsh which can be updated through a unified future other periodic data.Keywords: Iraqi Marshland, Environmental risk assessment, Model comparison.